Correlation between postpartum depression and omega-3, micronutrients - Mermer, Meltem; Şanlıer, Nevin (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
In recent years, attention has been called to the link between nutrition and mental health. Postpartum depression is an important depressive disorder which often arises 6 to 12 weeks after giving birth and can happen at any time within one year. Postpartum depression prevalence is around 20% worldwide. Genetic predisposition and environmental factors, as well as certain social, psychological and biological factors constitute risk factors for postpartum depression. While malnutrition is among the biological factors, there is a correlation between nutrients such as folic acid, vitamin B₁₂, vitamin D, iron, selenium, zinc, and n-3 fatty acids and psychological state. The nutrients that claim most attention relating to postpartum depression are n-3 essential fatty acids. Insufficient intake of n-3, folic acid, vitamins B and iron is observed in pregnant women. Failing to meet the needs of the mother due to malnutrition during pregnancy can increase the risk of depleting the body’s nutrient reserves and developing postpartum. This risk factor needs to be kept in check by determining and keeping track of the nutrient needs of the mother during the perinatal period.